Predicting Coping with Performance Failure by Self-Compassion and Growth Mindset in Professional Athletes - Toktas, Elif; Köse, Neşe (Health Nexus, 2025)
The objective of this study was to examine the predictive roles of self-compassion and growth mindset in coping with performance failure among professional athletes. This study employed a correlational descriptive design involving 396 professional athletes from Turkey. Participants were selected according to the Morgan and Krejcie (1970) table and completed standardized questionnaires measuring self-compassion, growth mindset, and coping with performance failure. Data analysis was conducted using SPSS-27. Pearson correlation was utilized to assess the relationships between coping with performance failure and each independent variable separately, and multiple linear regression analysis was conducted to evaluate the predictive power of self-compassion and growth mindset on coping with performance failure. Pearson correlation analysis indicated that coping with performance failure was positively and significantly correlated with self-compassion (r = .54, p < 0.01) and growth mindset (r = .48, p < 0.01). Multiple linear regression results revealed that self-compassion and growth mindset together significantly predicted coping with performance failure (R = .58, R² = .34, F(2, 393) = 101.63, p < 0.01). Both self-compassion (β = .44, t = 8.91, p < 0.01) and growth mindset (β = .29, t = 7.09, p < 0.01) were significant positive predictors, with self-compassion emerging as the stronger predictor. The findings highlight the critical roles of self-compassion and growth mindset in facilitating more adaptive coping with performance failure among professional athletes. Enhancing both emotional regulation through self-compassion and cognitive beliefs through growth mindset may contribute to improved resilience and performance outcomes in competitive sports settings.